2015
DOI: 10.1016/j.resuscitation.2015.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Temporal distribution of instability events in continuously monitored step-down unit patients: Implications for Rapid Response Systems

Abstract: AIM Medical Emergency Teams (MET) activations are more frequent during daytime and weekdays, but whether due to greater patient instability, proximity from admission time, or caregiver concentration is unclear. We sought to determine if instability events, when they occurred, varied in their temporal distribution. METHODS Monitoring data were recorded (frequency 1/20Hz) in 634 SDU patients (41,635 monitoring hours). Vital sign excursion beyond our MET trigger thresholds defined alerts. The resultant 1,399 al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The same group also published a study utilizing electronic alerts with automated pages going to nurses for patients showing signs of clinical deterioration on the wards (29). Similar studies have been published in step-down and ICU patients (30,31), and these real-time alerts may also help bridge the gap between when rapid response teams are typically alerted and when instability events actually occur (32). Our results suggest that utilizing the random forest model has the potential to markedly decrease false alarms compared to logistic regression.…”
Section: Discussionmentioning
confidence: 69%
“…The same group also published a study utilizing electronic alerts with automated pages going to nurses for patients showing signs of clinical deterioration on the wards (29). Similar studies have been published in step-down and ICU patients (30,31), and these real-time alerts may also help bridge the gap between when rapid response teams are typically alerted and when instability events actually occur (32). Our results suggest that utilizing the random forest model has the potential to markedly decrease false alarms compared to logistic regression.…”
Section: Discussionmentioning
confidence: 69%
“…Newer data-driven analytic techniques using machine learning algorithms can be employed for this to address these complex and often subtle confounders, by discovering numerous untapped hidden signals and patterns once used to be thought of as noise. Recent literature suggests that a data-driven approach based on machine learning algorithms could reveal telltale signs of impending instability **(79). The inherent heterogeneity and complexity of ICU data can be addressed by acquiring multivariate, high frequency, multi-source data as hemodynamic changes display a time-sensitive nature and nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] We have previously reported that CRI, when it occurs, is most likely to manifest in the hours closest to SDU admission. 13 However, there is limited guidance on what changes most commonly serve as the initial vital sign change (driver) preceding CRI or patient characteristics that confer added risk. Therefore, the purpose of this study was to describe admission characteristics, CRI drivers (defined as the first vital sign to cross threshold), and time to onset of initial CRI events in monitored SDU subjects.…”
Section: Introductionmentioning
confidence: 99%